2022
DOI: 10.3389/fneur.2022.895476
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow and Other Predictors of Responsiveness to Erenumab and Fremanezumab in Migraine—A Real-Life Study

Abstract: IntroductionMonoclonal antibodies (mAbs) showed efficacy in migraine prevention. The aim of this study was to check if baseline clinical parameters and cerebral blood flow (CBF) measured by transcranial Doppler (TCD) may help predict mAbs efficacy.MethodsElectronic charts of migraineurs treated with erenumab or fremanezumab, with baseline TCD evaluations were collected, including data on migraine type, pain localization, monthly migraine days (MMD), medication overuse headache (MOH), mean blood flow velocity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
1
23
2
Order By: Relevance
“…Our results suggest that ≥ 50% CGRPmAb response is significantly associated with older age, fewer MHD, and fewer prior treatment failures, and can be predicted based on age, total prior treatment failures, and immunorheumatologic medical history. Several parameters that are reportedly associated with response, such as medication overuse [11,17,19], unilateral pain localisation [15], medical history of psychiatric disease [14,20], and MMD [18], were not significantly different between responders and non-responders in the present study.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Our results suggest that ≥ 50% CGRPmAb response is significantly associated with older age, fewer MHD, and fewer prior treatment failures, and can be predicted based on age, total prior treatment failures, and immunorheumatologic medical history. Several parameters that are reportedly associated with response, such as medication overuse [11,17,19], unilateral pain localisation [15], medical history of psychiatric disease [14,20], and MMD [18], were not significantly different between responders and non-responders in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…The literature to date has shown that the response to CGRPmAbs is positively associated with a lower number of failed preventative medications [11][12][13][14], unilateral pain localisation [13][14][15], better response to triptans [13,16], lower number of monthly analgesic intakes at baseline [11,17,18], shorter duration of medication-overuse headache (MOH) [11,13,17,19], and lower body mass index (BMI) [13], and negatively associated with the existence of psychiatric conditions [14,20]. However, the results of these real-world studies have not always been consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several attempts, clear predictors of response could not be determined in the registration trials. In a few real-world studies, unilateral pain localization, and triptan responsiveness were positively associated with a better treatment response [ 17 21 ]. On the contrary, psychiatric comorbidities, a long disease duration and a high number of previously failed preventive treatments were associated with a lower response [ 17 , 18 , 22 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atogepant displays the largest potency difference (35-210 times more potent in human middle meningeal artery), which seems favorable in view of the cardiovascular profile. However, efficacy, as well as safety, also depend on many other factors, such as plasma-protein binding, dosing, dosing intervals, duration of receptor antagonism in vivo and metabolism of the drug, as well as patient characteristics, such as the potential predominance of CGRP in the pathophysiology of their migraine attacks [30,31] and/or genetic polymorphisms in the CGRP receptor gene components [32]. Telcagepant, ubrogepant and zavegepant show a Schild plot slope in h coronary arteries that does not differ from unity, whereas for atogepant, olcegepant and gepant, the Schild slope is significantly less than unity.…”
Section: Discussionmentioning
confidence: 99%